PERUBAHAN KEBIJAKAN LUAR NEGERI AMERIKA SERIKAT TERHADAP KUBA PADA MASA PEMERINTAHAN DONALD TRUMP TAHUN 2017-2019 - Nur Salamah; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research explains the cause of U.S. foreign policy changes to Cuba during the reign of Donald Trump in 2017-2019.  U.S. foreign policy against Cuba during the reign of Donald Trump is deemed to have made the U.S.-Cuba relationship worse. This is because U.S. foreign policy against Cuba during the Obama administration will be revamped by Donald Trump.            This research used Behavioralis perspective with the concept of national importance of Behavioralis's view. The theory used in this reaseacrh  was foreign policy theory according to Rosenau with the level of analysis of the group's policy-making. This research uses qualitative methods with data collection techniques done by collecting data in the form of written text in Journal, Books, official websites, media, as well as interviews to test research documents.            The result of this study was the change of foreign policy of the United States against Cuba in the form of Donald Trump's personality that was in-consistent and the environmental influence of the political group. U.S. foreign policy changes to Cuba during the reign of Donald Trump are trade restrictions, people-to-people travelers, and transactions. Furthermore the policy also reduced the US embassy staff in Havana and the Cuban embassy staff in Washington.